Factors affecting influenza vaccine uptake among healthcare providers at a tertiary hospital in Mysuru, India: a questionnaire-based survey - Naviya Kafle; Jantine van Wijlick; P. Chaithra Poonacha; P. Priyanka; Jiten Choudhury; N. Onkar Yadav; R. Nisarga; Rebecca D. Kehm; Logan Stuck; Christopher Pell; Anil S. Bilimale (Vaccine: X)
Background: Despite the annual burden of seasonal influenza in India and previous experiences with pandemics, influenza vaccination rates remain low among the general population and healthcare workers (HCWs). Although health authorities recommend vaccination for high-risk groups, including, awareness and coverage among these groups remain inadequate. Drawing on a cross-sectional questionnaire-based survey, this article examines influenza vaccine uptake and related socio-demographics, attitudes and practices among HCWs in a tertiary hospital in Mysuru, South India. Methods: A team of trained research assistants administered a questionnaire-based survey to 427 HCWs (response rate: 99 %). Statistical analyses, including bivariate and multivariate logistic regression, were performed. Results: Among the 427 HCWs surveyed, the influenza vaccination rate was 14 %, despite 82 % awareness rate. Vaccination rates varied significantly based on job roles, with physicians and physicians in training exhibiting the highest rates, and nurses and other health workers reporting zero vaccination rates. Regression analysis revealed that HCWs that perceived influenza as a serious disease were 2.77 times more likely to be vaccinated compared to those who perceived it as not serious or indicated being unsure, after adjusting for age, gender and position (95 % CI: 1.26 to 6.06). Conclusions: Influenza vaccination uptake among HCWs in Mysuru was low, particularly among nurses. The disease was often perceived as low risk. Targeted interventions, designed with collaboration with target groups to adapt to their needs, are crucial. Efforts to raise awareness about the risks of influenza and to enhance vaccine accessibility would further support increased uptake.